2001
DOI: 10.1177/027112140102100104
|View full text |Cite
|
Sign up to set email alerts
|

The Costs of Preschool Inclusion

Abstract: The purpose of this study was to examine the instructional costs of inclusive and traditional noninclusive special education services for preschool children with disabilities. Cost information was collected from five local education agencies in different parts of the country that provided inclusive and traditional special education service options. Within-agency comparisons suggested that inclusive models were generally less expensive or comparable in cost to traditional forms of special education. Cost featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…The cost benefit discourse reflects a capitalistic economic paradigm for evaluating the feasibility of inclusion. While on the larger scale, it might be argued that inclusion costs less than separate education in actual expense (Odom, Hanson, Lieber, Marquart, Sandall, Wolery & Chambers, 2001), the teachers' and school administration's disposition to weigh the costs and benefits precludes a human rights approach. Such an orientation would set aside these considerations in favor of the overriding values and visions of a just society.…”
Section: Discussionmentioning
confidence: 99%
“…The cost benefit discourse reflects a capitalistic economic paradigm for evaluating the feasibility of inclusion. While on the larger scale, it might be argued that inclusion costs less than separate education in actual expense (Odom, Hanson, Lieber, Marquart, Sandall, Wolery & Chambers, 2001), the teachers' and school administration's disposition to weigh the costs and benefits precludes a human rights approach. Such an orientation would set aside these considerations in favor of the overriding values and visions of a just society.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Odom et al (2001) examined the instructional costs of inclusive and traditional non-inclusive special education services for preschool children with disabilities. The researchers utilized three different surveys of 16 preschool programs to collect information on the cost of teaching students in the classroom (instructional costs).…”
Section: Budgetary Ramificationsmentioning
confidence: 99%
“…The results of Odom et al (2001) indicated that teachers' salaries were the largest expense in all of the programs. When the cost to the LEA was used as the basis of comparison, the inclusive settings were less expensive to run than the traditional service models.…”
Section: Budgetary Ramificationsmentioning
confidence: 99%
“…Growing amounts of research stemmed out of the concept of inclusion and questions regarding the benefits and drawbacks of inclusion were soon being studied. Undoubtedly, research has shown that inclusive settings provided benefits to both children with EOD and children without EOD (Bruder, & Brand, 1995;Stahmer, & Carter, 2005;Stahmer, Carter, Baker, & Miwa, 2003) and that, at least in the school setting, inclusive settings were equivalent in cost or less expensive to run when compared to specialized, segregated environments (Odom et al, 2001).…”
Section: The Importance Of Inclusion For Children With and Without Eodmentioning
confidence: 99%